Current insights in molecular characterization of non-alcoholic fatty liver disease and treatment - Che, Wensheng; Zhao, Ming; Li, Xiaoqing; Li, Chunlong; Cho, William C.; Yu, Shan (Frontiers in Endocrinology, 2022)
There is a continuously rising incidence of nonalcoholic fatty liver disease (NAFLD), in parallel with increasing incidence of metabolic diseases. NAFLD is a continuous process that contains simple nonalcoholic fatty liver and advanced nonalcoholic steatohepatitis. In turn, NAFLD may eventually develop into cirrhosis or liver cancer. NAFLD has intense relations with metabolic syndrome, type-2 diabetes mellitus, gut microbiota, and functional molecules such as AMPK, JNK, and PPARs with progressing and treatment of NAFLD. The most accepted and effective therapeutic strategy is still lifestyle intervention. Nowadays, some new medicines targeting specific molecules, such as farnesoid X receptor, PPARs, GLP-1 receptor, are discovered and have shown beneficial effects on NAFLD. In this review, we focus on the understanding of molecular mechanisms, and therapeutic approaches to NAFLD.